An analysis of National Cancer Institute-funded scale-up research - Vinson, Cynthia; Villalobos, Aubrey; Correa-Mendez, Margarita; Neta, Gila (Frontiers in Health Services, 2025)
BackgroundThe National Cancer Institute seeks to support cancer research to advance scientific knowledge that will “help all people live longer, healthier lives.” To do this, we need to understand how to effectively and efficiently scale-up evidence-based cancer control innovations (EBIs). We analyzed National Cancer Institute (NCI)-funded implementation science (IS) grants to understand gaps and opportunities for scale-up research.MethodsThe National Institutes of Health (NIH) Query, View, and Report (QVR) system was used to identify NCI-funded IS grants focused on scale-up since 2016. Key search terms were identified, and two coders reviewed specific aims to identify IS and scale-up grants. Eligible grants were coded for study characteristics, including administrative, cancer-related, and scale-up related features using Microsoft Excel and iSearch.ResultsOf the 61 grants initially identified, 17 were included. Approximately one-third of the grants were conducted abroad (n = 6). Most examined factors related to scale-up (e.g., barriers/facilitators, context) (n = 11). Nine studies assessed the costs and benefits of the scaled-up delivery of an EBI, and seven studies evaluated an implementation strategy for EBI scale-up. Most focused on prevention (n = 11), with seven focusing on screening. Cervical cancer (n = 6) was the most frequently studied cancer type. Most of the research took place in healthcare settings (n = 11).ConclusionsThe NCI has funded a limited number of IS grants focused on scale-up. This analysis helps identify the current scope of the NCI portfolio and enables exploration of gaps and opportunities for future research on scale-up across the cancer continuum.